2008
DOI: 10.1101/gr.069674.107
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the immune gene repertoire of amphioxus reveals extraordinary innate complexity and diversity

Abstract: It has been speculated that before vertebrates evolved somatic diversity-based adaptive immunity, the germline-encoded diversity of innate immunity may have been more developed. Amphioxus occupies the basal position of the chordate phylum and hence is an important reference to the evolution of vertebrate immunity. Here we report the first comprehensive genomic survey of the immune gene repertoire of the amphioxus Branchiostoma floridae. It has been reported that the purple sea urchin has a vastly expanded inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
288
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(301 citation statements)
references
References 57 publications
12
288
1
Order By: Relevance
“…NLR (CLR) proteins play an important role in immunity, cell death, and disease in vertebrates, and their close counterparts exert a similar action in plants (27); our results indicate that the negative regulatory functions shown in mammals by some members of this protein family are conserved across distant evolutionary lineages and associated with different proteins, which share the presence of a LRR domain. This is not surprising, as LRR domains are one of the most commonly occurring domains in proteins associated with innate immunity (35,36); moreover, the function of many LRR domains is to provide a structural framework for protein-protein interactions (37). The down-regulation of these inhibitory proteins upon immune challenge is required to trigger a defense response in mammals and likely plays a pivotal role in preventing an overzealous reaction that could be detrimental to the host (27).…”
Section: Resultsmentioning
confidence: 99%
“…NLR (CLR) proteins play an important role in immunity, cell death, and disease in vertebrates, and their close counterparts exert a similar action in plants (27); our results indicate that the negative regulatory functions shown in mammals by some members of this protein family are conserved across distant evolutionary lineages and associated with different proteins, which share the presence of a LRR domain. This is not surprising, as LRR domains are one of the most commonly occurring domains in proteins associated with innate immunity (35,36); moreover, the function of many LRR domains is to provide a structural framework for protein-protein interactions (37). The down-regulation of these inhibitory proteins upon immune challenge is required to trigger a defense response in mammals and likely plays a pivotal role in preventing an overzealous reaction that could be detrimental to the host (27).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of immune-related genes in the amphioxus genome identified a TICAM2-like molecule [12]. However, the full-length sequence revealed that the protein architecture of bbtTICAM is more similar to vertebrate TICAM1, including its length, position of the TIR domain, the RHIM in the C terminus, and the potential TRAF2-binding motif in the N terminus.…”
Section: Discussion Bbtticam Is the Earliest Ortholog Of Vertebrate Tmentioning
confidence: 99%
“…MyD88, the first-identified TIR adaptor in mammals, is also present in poriferans [7], cnidarians [8], Drosophila [9], sea urchin [10,11], and amphioxus [12]. The direct interaction of MyD88 with TLRs in Drosophila and amphioxus suggests that this pathway is functionally conserved during evolution [13].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations